Pregnancy in patients presenting with hyperprolactinaemia. Issue 6193 (29th September 1979) - Thorner, M O; Edwards, C R; Charlesworth, M; Dacie, J E; Moult, P J; Rees, L H; Jones, A E; Besser, G M
Abstract : Ninety-two pregnancies occurred in 76 hyperprolactinaemic patients treated with bromocriptine. Half conceived within three months of attempted conception. There was no evidence of an increased rate of spontaneous abortion, fetal abnormality, or multiple pregnancy; the three twin pregnancies occurred in women who were additionally treated with clomiphene and human chorionic gonadotrophin. Thirty-one patients had radiological evidence of a pituitary tumour; 14 with major radiograph changes in the pituitary fossa or serum prolactin concentrations greater than 100 ng/ml received pituitary irradiation before conception. None of the latter showed evidence of enlargement of the tumour during pregnancy. In contrast two of the four patients with similar tumours but who were not irradiated developed visual field defects, one with gross destruction of the pituitary fossa. Prophylactic treatment to limit subsequent tumour expansion during pregnancy in patients with prolactinomas is indicated, and pituitary irradiation before conception appears to be a safe and effective method to achieve this goal.